Physician Orders for Life Sustaining Treatment in US Nursing Homes: A Case Study of CRNP Engagement in the Care Planning Process - Gerald A. Hartle; David G. Thimons; Joseph Angelelli (Hindawi Limited, 2014)
This case study describes changes in Physician Orders for Life Saving Treatment (POLST) status among long-stay residents of a US nursing home who had a certified registered nurse practitioner (CRNP) adopt the practice of participating in nursing home staff care plan meetings. The CRNP attended a nonrandomized sample of 60 care plan meetings, each featuring a review of POLST preferences with residents and/or family members. Days since original POLST completion, Charlson Comorbidity Index score, number of hospitalizations since index admission, and other sociodemographic characteristics including religion and payer source were among the data elements extracted via chart review for the sample as well as for a nonequivalent control group of 115 residents also under the care of the medical provider group practice at the nursing home. Twenty-three percent (n=14) of the 60 care conferences attended by the CRNP resulted in a change in POLST status after consultations with the resident and/or family. In all cases, POLST changes involved restated preferences from a higher level of intervention to a lower level of intervention. Fifty-nine percent of the CRNP-attended conferences resulted in the issuance of new medical provider orders. CRNP participation in care conferences may represent a best practice opportunity to revisit goals of care with individuals and their family members in the context of broader interprofessional treatment planning.